1988
DOI: 10.1139/v88-255
|View full text |Cite
|
Sign up to set email alerts
|

Cyclobutene photochemistry. Involvement of carbene intermediates in the photochemistry of alkylcyclobutenes

Abstract: . Can. J. Chem. 66, 1571 (1988). The photochemistry of 1,3,3,4-and 1,3,4,4-tetramethylcyclobutene has been investigated in pentane solution with monochromatic far ultraviolet (185, 193, and 214 nm) light sources, as well as in methanol solution with 214-nm excitation. Photolysis of each of the two isomeric cyclobutene derivatives results in competitive electrocyclic ring opening (yielding mixtures of stereoisomeric dienes in each case), fragmentation to yield propyne and methyl-2-butene, and isomerization to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…[lo]). Similar investigations of the photochemistry of a wide variety of mono-, bi-, and tricyclic alkylcyclobutene derivatives have been reported since our initial study (23)(24)(25)(26)(27)(28)(29), and indicate that the nonstereospecificity of the photochemical ring opening reaction is quite general. The results of these studies will be discussed in detail throughout this account.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…[lo]). Similar investigations of the photochemistry of a wide variety of mono-, bi-, and tricyclic alkylcyclobutene derivatives have been reported since our initial study (23)(24)(25)(26)(27)(28)(29), and indicate that the nonstereospecificity of the photochemical ring opening reaction is quite general. The results of these studies will be discussed in detail throughout this account.…”
supporting
confidence: 84%
“…[ l I]), has been investigated directly (24). Cyclopropylcarbenes are known to undergo ring contraction to yield cyclobutenes in addition to fragmenting to an alkene and acetylene.…”
Section: Scope and Rnechanism Of The Cycloreversion Reactionmentioning
confidence: 99%
“…There is a similar substituent effect on the relative energies of the n , n * and n,R(3s) states in alkenes, as determined by gas-phase UV absorption (12) and fluorescence emission spectroscopy (13), and the n,R(3s) state is the lowest energy state in tri-and tetrasubstituted alkenes (12,14). We have recently reported evidence for carbene involvement in cyclobutene photochemistry (15). Although we were unable to quantify the extent of carbene involvement in those cases, the results suggest that the n,R(3s) state does contribute to the photochemistry of alkylcyclobutenes, as it does in the case of simpler alkenes.…”
Section: Introductionmentioning
confidence: 63%
“…Cis-and trans-1,3,4-trimethylcyclobutene (cis-and trans-3) and cis and trans-1,2,3,4-tetramethylcyclobutene (cis-and trat~s-4) were prepared by routes similar to those published previously for related methylated cyclobutenes (1,15), starting with the acetophenonesensitized photocycloadditions of citraconic anhydride or dimethylmaleic anhydride (prepared by the method of Baumann and Bossard (26)) with 2-butene (17), followed by hydrolysis of the bicyclic anhydrides and bisdecarboxylation of the resulting dicarboxylic acids with lead tetraacetate (27). In both syntheses, the two cyclobutene isomers were obtained in similar yields.…”
Section: Preparation Of Compoundsmentioning
confidence: 99%
“…From this it has been concluded that ring opening is a .rr,.rr* singlet state process, while cycloreversion arises from an excited singlet state with substantial (.rr,R(3s)) Rydberg character. The observation of skeletal rearrangements in the photochemistry of asymmetrically substituted, monocyclic alkylcyclobutenes suggests that cycloreversion may proceed via cyclopropyl carbene intermediates formed by ring contraction (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%